(untitled) (Faridpur Medical College Journal, 2015)
Hepatitis C virus is a major cause of chronic hepatitis and is responsible for majority of liver transplantation worldwide. It has got no vaccine for prevention. Interferon containing regimen was the only management options for treatment of Hepatitis C virus till last year. Due to side effect profile and treatment cost this treatment options was not reachable for general population. Besides, response rate was not so satisfactory (Genotype 1, 40-50%, Genotype 2 & 3, 70-80%). New oral antivirals were introduced in 2014 which has got little side effect profile as well as good treatment response rate (80-95%). These new drugs with their different combination regimens along with indications, contraindications and treatment monitoring of Hepatitis C virus are discussed briefly in this review. Faridpur Med. Coll. J. 2014;9(2): 92-97